Impact of the usage of information technology tools on knowledge management process: a case of ministry of labour, United Arab Emirates (UAE) - Hadeeba Alnuaimi, Salem Obaid Salem (2023)
The usage of IT tools is essential for knowledge management; however, studies reported that the role of IT in the knowledge management process has not been that successful mainly due to the improper usage and integration of information technology into knowledge management. In the UAE, there is no clear evidence for any study that has investigated the usage of IT tools in enhancing the KM process. Accordingly, the current study aims to identify IT tools and the effect of their usage on the KM process (knowledge sharing and knowledge application) in government organizations in the UAE. The current study employed a quantitative research design, and the data were collected through a survey. The sample size of the research is 269, who were selected based on convenience non-probability random sampling. The data was analysed using SPSS and PLS-SEM. The first research objective led to the identification of Cloud Computing (CC), Online Conferencing Systems (OCS), and Mobile Technology (MT) as the IT tools that affect the KM process. This objective was supported by the analysis of the mean values of each factor through SPSS, which showed that these factors have high mean values as follows: 3.988 for Cloud computing, 4.162 for OCS, and 4.146 for MT. The second research objective showed that only the usage of MT has a significant relationship with the knowledge management process (knowledge sharing and knowledge application), while the two variables CC and OCS do not have a significant relationship with knowledge sharing and knowledge application in government agencies in the UAE. The third research objective showed that Organization Culture (OC) significantly mediates the relationship between CC, MT, and OCS and the knowledge management process (knowledge sharing and knowledge application), but it did not significantly mediate the relationship between the CC and knowledge application. This research contributes to the understanding of the relationship between the usage of IT tools and the KM process in emerging countries since the usage of Information Technology tools is significant in supporting the KM process in organizations, especially since organizational culture is essential in supporting the KM process with the usage of IT tools. Also, policy and decision-makers need to consider the usage of IT tools and promote it in the organizational culture to support the enhancement of the KM process in the organization